Correlation between phase content and mechanical properties of SiCw- ZTA composites sintered by SPS. Issue 11 (1st June 2021) - Niu, Lijuan; Li, Shufen; Zhu, Yabin; Chai, Jianlong; Liu, Yiwen; Shen, Tielong; Jin, Peng; Zhang, Hongpeng; Xie, Erqing; Wang, Zhiguang
Abstract: The zirconia toughened alumina (ZTA) composites have been widely used as an engineering material in many application areas due to their remarkable mechanical properties. However, the fracture toughness of ZTA does not generally meet the requirements of aerospace, machinery and other fields. In this study, the SiC whiskers (SiCw ) have been incorporated in the ZTA composites to improve the fracture toughness. The SiCw employed in this study mainly consist of the β phase, with a small fraction of the α phase. The effect of the SiCw content and sintering temperature on the microstructure and mechanical properties of the SiCw -ZTA (ZASw ) composites has been systematically studied. The incorporation of SiCw is noted to reduce the density of the ZASw composites. On enhancing the SiCw content, the Vickers hardness and fracture toughness of the composites initially decrease, followed by an increase. However, the flexural strength of the composites increases with the SiCw content. At a SiCw content of 10.0 vol %, the strength, hardness and toughness are observed to reach the maximum values. On enhancing the sintering temperature, the strength and hardness of the composites are observed to remain nearly constant, while the toughness of the composites is increased.